2018
DOI: 10.7358/neur-2018-024-balc
|View full text |Cite
|
Sign up to set email alerts
|

EEG hyperscanning and behavioral synchronization during a joint actions

Abstract: Brain-to-brain coupling during cooperation is a core question of study on social interactions. The aim of the present study was to investigate the neural basis of interbrain cooperation and the cognitive performance underlying the execution of jointactions by using EEG coherence measures. Synchronicity of the cognitive variables (response times, RTs, and error rates, ERs) in response to an attentional task, intersubjective coherence analysis on EEG frequency bands, and correlational measures between cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
1
11
0
1
Order By: Relevance
“…A growing body of studies using a new brain imaging technique-hyperscanning, 26 which allows measurement of the activity of multiple brains simultaneously-has revealed that neuronal oscillations are also influenced by social dynamics. 27,28 In particular, natural social interactions produce a brain-to-brain synchrony in neural oscillations during natural social interactions that is linked with behavioral synchrony. In other words, synchronized neuronal oscillations coordinate people physically by regulating how and when their bodies move together.…”
Section: Group Identification Collective Performance and Creativitymentioning
confidence: 99%
“…A growing body of studies using a new brain imaging technique-hyperscanning, 26 which allows measurement of the activity of multiple brains simultaneously-has revealed that neuronal oscillations are also influenced by social dynamics. 27,28 In particular, natural social interactions produce a brain-to-brain synchrony in neural oscillations during natural social interactions that is linked with behavioral synchrony. In other words, synchronized neuronal oscillations coordinate people physically by regulating how and when their bodies move together.…”
Section: Group Identification Collective Performance and Creativitymentioning
confidence: 99%
“…The motor synchronization application makes up 23% (14/60) of the research done with the MEG/EEG neuro-imaging methodology [41,58,[102][103][104][105][106][107][108][109][110][111][112][113]. The goal of these studies was to look at how participants are able to coordinate their actions with each other.…”
Section: Motor Synchronizationmentioning
confidence: 99%
“…The goal of these studies was to look at how participants are able to coordinate their actions with each other. This was most commonly done by asking participants to perform a motor task such as rhythmically tapping their fingers [41,104,105], following someone's lead (imitation) to tap the sensors at the same time [102,106,[108][109][110], or other motor/selective attention tasks [68,107,[111][112][113]. Motor synchronization studies were also done via a computer by asking participants to try to coordinate their response times to different matching/shapes games.…”
Section: Motor Synchronizationmentioning
confidence: 99%
“…Infatti, l'applicazione dell'hyperscanning si è recentemente evoluta passando dall'osservazione dei meccanismi di sintonizzazione neurale e corporea durante lo svolgimento di compiti interattivi (Montague et al, 2002) o economici (King-Casas et al, 2005) a contesti d'interazione reali, come: esibizioni musicali (Lindenberger, Li, Gruber, & Müller, 2009); situazioni cooperative o competitive, che richiedono la sincronizzazione o desincronizzazione delle risposte degli individui durante l'esecuzione di un compito attentivo (Balconi & Vanutelli, 2018); scambi comunicativi che implicano l'osservazione e la riproduzione di differenti categorie di gesti e contesti prosociali, in cui agli individui viene richiesto di svolgere un compito congiunto prima e dopo lo scambio di un dono (Balconi & Vanutelli, 2017a;Balconi et al, 2019;Balconi et al, 2020a).…”
Section: Creatività Dove Ancora Non Arriva L'algoritmo Bruna Navaunclassified